Evaluating the Causal Association Between Educational Attainment and Asthma Using a Mendelian Randomization Design - Li, Yunxia; Chen, Wenhao; Tian, Shiyao; Xia, Shuyue; Yang, Biao (Frontiers in Genetics, 2021)
Asthma is a common chronic respiratory disease. In the past 10 years, genome-wide association study (GWAS) has been widely used to identify the common asthma genetic variants. Importantly, these publicly available asthma GWAS datasets provide important data support to investigate the causal association of kinds of risk factors with asthma by a Mendelian randomization (MR) design. It is known that socioeconomic status is associated with asthma. However, it remains unclear about the causal association between socioeconomic status and asthma. Here, we selected 162 independent educational attainment genetic variants as the potential instruments to evaluate the causal association between educational attainment and asthma using large-scale GWAS datasets of educational attainment (n=405,072) and asthma (n=30,810). We conducted a pleiotropy analysis using MR-Egger intercept test, and the MR pleiotropy residual sum and outlier (MR-PRESSO) test. We performed a MR analysis using inverse variance weighted, weighted median, MR-Egger, and MR-PRESSO. The main analysis method IVW indicated that each 1 SD increase in educational attainment (3.6 years) could reduce 35% asthma risk (OR=0.65, 95% CI 0.51-0.85, P=0.001). Importantly, evidence from other MR methods further supported this finding including weighted median (OR=0.55, 95% CI 0.38–0.80, P=0.001), MR-Egger (OR=0.48, 95% CI 0.16–1.46, P=0.198), and MR-PRESSO (OR=0.65, 95% CI 0.51-0.85, P=0.0015). Meanwhile, we provide evidence to support that educational attainment protects against asthma risk dependently of cognitive performance using multivariable MR analysis. In summary, we highlight the protective role of educational attainment against asthma. Our findings may have public health application, and deserve further investigation.